281 HEME OXYGENASE ACTIVITY IN THE MOUSE PLACENTA DURING FETAL DEVELOPMENT. (1st January 2006) - Zhao, H.; Wong, R. J.; Morioka, I.; Kalish, F. A.; Stevenson, D. K.
Abstract : The placenta is the organ through which respiratory gases, nutrients, and wastes are exchanged between maternal and fetal systems. The near-maximal dilation of uteroplacental arteries is required to facilitate successful placental perfusion. Since carbon monoxide (CO) has vasodilatory properties, it has been suggested to play a role in regulating placental vascular tone. The primary source of endogenous CO production is through the heme degradation pathway, which is catalyzed by heme oxygenase (HO), to produce CO, biliverdin, and iron. Our objective was to investigate the presence of HO enzyme activity in the placenta during fetal development. Maternal livers and placentas were collected at different gestation ages and HO activity was quantitated using gas chromatography. Significant HO activity was found in the mouse placenta at levels greater than that of maternal livers. The highest HO activity was found in placentas at gestational age E14 and levels progressively decreased with advanced pregnancy (see Table ). To investigate the contribution of HO to placental CO production, we administered tin mesoporphyrin (SnMP), a potent HO inhibitor, at a dose of 30 μM, or vehicle (sham control) via tail vein injections into FVB mice at various stages of pregnancy. Two hours after treatment, placentas and fetal and maternal livers (positive control) were measured for HO activity [mean ± SD pmol CO formed/hr/mg fresh weight (% of control)] as follows: Placental HO activity was almost completely inhibited by SnMP treatment. In addition, HO activity in fetal livers peaked at age E16 and was only slightly inhibited by SnMP, suggesting a partial crossing of SnMP through the mouse fetoplacental barrier. Therefore, we conclude that HO is present in the mouse placenta at high amounts and supports the hypothesis that the formation of heme-derived CO may play a role in placental function. This work was supported in part by National Institutes of Health grant #HD58013.